Analisis Keterampilan Servis Bawah Dan Servis Atas Bola Voli Pada Siswa Kelas V Di SD Negeri 76 Kota Bengkulu - Albanus, A. Albert; Asnawati, Asnawati; Syaputra, Roni (Educative Sportive, 2024)
This study aims to analyse the skills of lower service and upper service of volleyball for class v students at SD Negeri 76 Bengkulu City. This type of research is Quantitative Descriptive with test method with a sample size of 24 class v students at SD Negeri 76 Bengkulu City. The results of research on the analysis of lower service skills and volleyball upper service in class v students at SD Negeri 76 Bengkulu City are in the sufficient category. In the lower serve test with the highest score of 33, the lowest was 9 and the average was 19.46. In the ‘Excellent’ category as many as 0 people, the ‘Good’ category as many as 2 people with a percentage of 8%, the ‘Fair’ category as many as 13 people with a percentage of 54%, the ‘Less’ category as many as 9 people with a percentage of 38% and those who get in the ‘Very Poor’ category as many as 0 people. Furthermore, the results of the upper service test data are in the ‘Excellent’ category as many as 0 people, the ‘Good’ category as many as 1 person with a percentage of 4%, the ‘Enough’ category as many as 12 people with a percentage of 50%, the ‘Less’ category as many as 11 people with a percentage of 46% and those who get in the ‘Very Poor’ category as many as 0 people.